1997
DOI: 10.1557/jmr.1997.0010
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical and tribological characterization of doped single-crystal silicon and polysilicon films for microelectromechanical systems devices

Abstract: Microelectromechanical systems (MEMS) devices are made of doped single-crystal silicon, LPCVD polysilicon films, and other ceramic films. Very little is understood about tribology and mechanical characterization of these materials on micro-to nanoscales. Micromechanical and tribological characterization of p-type (lightly boron-doped) single-crystal silicon (referred to as "undoped"), p 1 -type ( boron doped) single-crystal silicon, polysilicon bulk, and n 1 -type (phosphorous doped) LPCVD polysilicon films ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
122
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(136 citation statements)
references
References 35 publications
13
122
0
1
Order By: Relevance
“…Although, the friction coefficient between diamond and InP remains unknown, 39 this result is in good agreement with the commonly observed value of 0.1 for the friction of diamond on semiconductor surfaces. 40 An AFM topographical investigation was carried out on a scratch at a load of 0.4 mN to assess the deformation at the nanometer scale and the results are presented in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Although, the friction coefficient between diamond and InP remains unknown, 39 this result is in good agreement with the commonly observed value of 0.1 for the friction of diamond on semiconductor surfaces. 40 An AFM topographical investigation was carried out on a scratch at a load of 0.4 mN to assess the deformation at the nanometer scale and the results are presented in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows a photo of the Ni-Si wafer prior to testing. The hardness of Si is 13 GPa [16], SiO 2 is 9 GPa [17], and Ni is 600 MPa [18]. The sample was rinsed with acetone for 20 minutes in an ultrasonic cleaner prior to the friction test.…”
Section: Methodsmentioning
confidence: 99%
“…0.64 GPa, 16) but less than that of the Si (100) substrate (13 GPa) 14) due to the presence of the Au layer. Li et al 18,19) examined the hardness of undoped silicon, p þ -type silicon, polysilicon bulk and n þ -type polysilicon film using a nanoindentation technique at loads varying from 0.2 to 15 mN. Their results showed that the polysilicon bulk specimen exhibited the highest hardness of around 13 GPa, followed by the undoped Si(100), the n þ -type polysilicon film, and finally the n þ -type silicon, with a hardness of around 5 GPa.…”
Section: (B)mentioning
confidence: 99%